PERCEPTION AND MOTIVATION OF STUDENTS ON ENGLISH WRITING LANGUAGE LEARNING THROUGH GOOGLE CLASSROOM - Neli Nurhavni; Sintia Nur Rohmawati; Naf’an Tarihoran (Journal Of Language Education and Development (JLed), 2026)
This research examines how students view and are motivated by Google Classroom in the context of learning to write in English. A quantitative method was used to gather information through a questionnaire sent to 21 participants via Google Forms. The survey included 10 statements organized into two categories: students’ perceptions and their motivation. Results indicate that a majority of students hold favorable views of Google, Classroom, characterizing it as beneficial, effective, and user friendly. The platform supports access to educational resources, submission of assignments, and communication with instructors, thus aiding in a more structured learning experience. Regarding motivation, the findings suggest that Google Classroom boosts both internal and external motivation, prompting students to engage more actively in writing tasks. Nonetheless, issues like unreliable internet connections and slow notifications were mentioned, which could somewhat influence students’ experiences. In summary, the research concludes that Google Classroom serves as a valuable resource for enhancing the learning of English writing by fostering positive perceptions and motivation among students.